2011
DOI: 10.1186/1471-2458-11-193
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions and attitudes toward thalassaemia: Influencing factors in a multi-racial population

Abstract: BackgroundThalassaemia is a common public health problem in Malaysia and about 4.5 to 6% of the Malays and Chinese are carriers of this genetic disorder. The major forms of thalassaemia result in death in utero of affected foetuses (α-thalassaemia) or life-long blood transfusions for survival in β-thalassaemia. This study, the first nationwide population based survey of thalassaemia in Malaysia, aimed to determine differences in public awareness, perceptions and attitudes toward thalassaemia in the multi-racia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(108 citation statements)
references
References 21 publications
8
92
7
1
Order By: Relevance
“…Which is on higher side than a Malaysian study in which 76.4% participants had heard about thalassemia, previously in which majority were of females and from rural area 15 . Which is also much on higher side than a study done in turkey in which 57.7% participants had heard about thalassemia, previously 16 .…”
Section: Fig 2: Awareness About Thalassemia Prevention (N=130) 4 Discmentioning
confidence: 88%
“…Which is on higher side than a Malaysian study in which 76.4% participants had heard about thalassemia, previously in which majority were of females and from rural area 15 . Which is also much on higher side than a study done in turkey in which 57.7% participants had heard about thalassemia, previously 16 .…”
Section: Fig 2: Awareness About Thalassemia Prevention (N=130) 4 Discmentioning
confidence: 88%
“…In a cross-sectional survey among 3,723 members of the general public in Malaysia (Wong et al 2011), only 36.6 % were supportive of selective termination of foetuses diagnosed with thalassaemia major. As these households have no affected children, many may assume that parents with thalassaemic children will be more inclined to terminate affected pregnancies having personally raised a thalassaemic child which leads to greater awareness of the suffering that this condition can cause.…”
Section: Discussionmentioning
confidence: 99%
“…Studies addressing the acceptance of these measures have been done in Muslim-majority countries such as Iran (Karimi et al 2010), Pakistan (Gilani et al 2007), Lebanon (Zahed and Bou-dames 1997) and Saudi Arabia (Alkuraya and Kilani 2001) but are relatively scarce in Malaysia. A Malaysian survey among the general lay public documented not only a low level of knowledge about thalassaemia but it revealed that only 36.6 % of participants accepted selective termination of affected foetuses (Wong et al 2011) with the Malays less likely to accept abortion compared to the Chinese and Indians. Although the reasons were not explored further, it was perceived that cultural and religious restrictions contributed to the Malay participants' rejection of abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, preconceptional carrier screening is voluntary when it occurs in high schools and more often mandatory when applying for a marriage license (described as pre-marital screening) (Cousens et al 2010). These seem to be acceptable to the communities in which these approaches exist such as in Bahrain (Al Arrayed and Al Hajeri 2010) or in Malaysia where these might be implemented (Wong et al 2011a(Wong et al , 2011b. However, in the Netherlands where a screening program is not offered, there appeared to be a reluctance by GPs and midwives to facilitate the testing of at-risk ethnic groups, which could be a barrier to implementation (Weinreich et al 2009).…”
Section: Carrier Screening For Haemoglobinopathiesmentioning
confidence: 99%